Strategies for Fostering Self-Directed Learning Used by English Language Education Lecturers at Esa Unggul University - Elmawati; Lutfiyah (International Journal Labs, 2026)
This study investigates the strategies used by English Language Education lecturers at Esa Unggul University to foster self-directed learning (SDL) among students. Employing a qualitative descriptive design, data were collected through semi-structured interviews, classroom observations, and document analysis with four lecturers selected based on SDL-related criteria. Thematic analysis using ATLAS.ti revealed ten strategies: collaborative learning, formative assessment, technology integration, cooperative learning, metacognitive skills development, task ownership, constructive feedback, problem-based learning, resource utilization, and climate setting. Collaborative learning, formative assessment, and technology integration emerged as the most consistently applied across instruments, reflecting a shift from teacher-centered to student-centered approaches that encourage peer collaboration, digital engagement, and formative feedback. However, strategies that develop autonomy and metacognitive regulation were less evident in classroom practices. The findings highlight the need for continuous professional development to strengthen lecturers’ capacity to integrate deeper SDL principles into their teaching, thereby supporting students’ independence, critical thinking, and lifelong learning skills.